Within my heart - Alexander, Tamera (Alexander, Tamera. Timber Ridge reflections., 2010)
Widow Rachel Boyd, struggling to keep her ranch afloat and raise her two young sons, squelches any feelings she might have for Rand Brookston, Timber Ridge's physician and reluctant veterinarian. But when she's courted by a wealthy client of the local resort, she faces a choice: self-sufficiency and security or the risk inherent in the deepest of loves.